Case report: A rare case of pulmonary mucormycosis caused by Lichtheimia ramosa in pediatric acute lymphoblastic leukemia and review of Lichtheimia infections in leukemia - He, Guo-qian; Xiao, Ling; Pan, Zhen; Wu, Jian-rong; Liang, Dong-ni; Guo, Xia; Jiang, Ming-yan; Gao, Ju (Frontiers in Oncology, 2022)
Mucormycosis caused by Lichtheimia ramosa is an emerging and uncommon opportunistic infection in patients with hematological malignancies, with high mortality rates. Herein, we first report a case of pulmonary mucormycosis with Lichtheimia ramosa in a 3-year-old girl recently diagnosed with B-cell acute lymphoblastic leukemia. The diagnosis was made using computerized tomography of the lung, metagenomic next-generation sequencinging (mNGS) of blood and sputum specimens, and microscopic examination to detect the development of Lichtheimia ramosa on the surgical specimen. She was effectively treated after receiving prompt treatment with amphotericin B and posaconazole, followed by aggressive surgical debridement.. In our case, the fungal isolates were identified as Lichtheimia ramosa using mNGS, which assisted clinicians in quickly and accurately diagnosing and initiating early intensive treatment. This case also indicated the importance of strong clinical suspicion, as well as aggressive antifungal therapy combined with surgical debridement of affected tissues.